Seizures in Pediatric Intensive Care Unit : A Retrospective Study - sabti, wijdan (Karbala Journal of Medicine, 2020)
background: The aim of our study was to retrospectively evaluate all the required admission to PICU to determine the etiology, clinical outcome. Methods : A total of 378 children were admitted from January 2019 to January 2020, 40 patients were eligible, Age ranged above one month to 16 years. Seizures were organized epileptic or acute symptomatic, pediatric risk factors, classification of diagnosis, description and duration of convulsion, medications given to the patients with duration of admission to ICU and immediate Outcome . Results : The male to female ratio 1, mean age was 14.6 months, the most common causes of seizures were acute symptomatic, most frequent coexistent diagnosis was infectious diseases and 70% progress to status epilepticus. Seizures were generalized in (28) 70% patients, (12) 30% had focal. Intravenous phenytoin and phenobarbiton was second line of therapy in 57.5% . Acute symptomatic seizures were usually new onset, and duration was shorter. Epileptic seizures tended to be recurrent and were likely to progress to status epilepticus. However type of seizures didn’t change severity of the disease, also laboratory test results, requirement for mechanical ventilation, duration of admission and mortality were not significant between epileptic/ acute symptomatic patients. Conclusion: Seizure in critically ill children ,which may evolve in to status epilepticus is an important condition that require attention regardless of cause .Intensified educational programs for PICU physician and international guidelines are necessary for a more efficient approach to children with seizures.